-2+v(-1)+3=0

Simple and best practice solution for -2+v(-1)+3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+v(-1)+3=0 equation:


Simplifying
-2 + v(-1) + 3 = 0

Reorder the terms for easier multiplication:
-2 + -1v + 3 = 0

Reorder the terms:
-2 + 3 + -1v = 0

Combine like terms: -2 + 3 = 1
1 + -1v = 0

Solving
1 + -1v = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -1v = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -1v = 0 + -1
-1v = 0 + -1

Combine like terms: 0 + -1 = -1
-1v = -1

Divide each side by '-1'.
v = 1

Simplifying
v = 1

See similar equations:

| -13.45=p-12.96 | | 2w+12-0.1w=31 | | -15t^2+105t+10=250 | | -5x-9=-x-9 | | 0.07r-5=0.03r+1 | | -t^2+vt+3=0 | | 100t+60=440 | | 0.2n-4=12 | | x+4+x+4+x+4= | | 0.5g+8=11 | | x^2+13x-90=0 | | X(x+1)=420 | | 4x-2=0+6x | | 0.5+8=11 | | 2c-3=17 | | 2x-8y=7 | | 3W-19-0.5w=31 | | 29x=14 | | 16-3x=-(2y-10) | | 2x^2+2y^2+4y=0 | | 8x+5y=33 | | -1.66666x=-6 | | 1.5n=67.5 | | -10-3x+2x=-10 | | 7p+4=5p-4 | | 3(p+5)=4-p | | 6x^2-7x=2 | | -4n=7(6-n) | | 12+8x+t-7x= | | 3x^2-2X+35=0 | | 3r+9(r-2)=7 | | y+3+(180-y+3)=180 |

Equations solver categories